Clinical manifestation and outcomes of children with hypertrophic cardiomyopathy in Kosovo - Bejiqi, Ramush A.; Retkoceri, Ragip; Zeka, Naim; Vuçiterna, Armend; Mustafa, Aferdita; Maloku, Arlinda; Bejiqi, Rinor (The Turkish Journal of Pediatrics, 2020)
Background and Objectives. Identification of the manifestations, assessment and follow up of children with hypertrophic cardiomyopathy (HCM) by transthoracic echocardiography may be important for clinical management and our understanding of pathogenesis. Methods. We present a comprehensive analysis of 43 children seen in Kosovo, 23 were male, aged between 4 months and 9 years at first presentation (median of 2 years and 3 months). Results. Cardiac failure, seen in almost half of them, was the most common presenting feature. At admission, the chest x-ray revealed an increased cardiothoracic ratio, to a mean of 72% in 6 infants and to 65% in 37 older children. Measured by transthoracic echocardiography, 28 children had asymmetric hypertrophy of left ventricle while 15 had concentric hypertrophy. Left ventricular ejection fraction was depressed in 21 children. Patients with cardiac failure received various combinations of diuretics, B-blockers, ACE inhibitors and anticoagulant therapy (aspirin). Death occurred in 8 children, in 4 of them shortly after admission, the other 4 left Kosovo and continued examination and treatment abroad Kosovo; their death has been confirmed by family members. The remaining 32 were followed- up for a mean 42 months, with a range from 5 to 115 months. Surgical intervention was not performed to any of them, despite the clinical and echocardiography indications due to a limitation of resources. Recovery was noted in 14 children but still requiring anti-heart failure medications. Slightly over two-fifths died. Of those with asymmetric form, 45% died, half of those presenting in infancy, and 89% of those who presented at admission with signs of cardiac failure. Conclusion. The results of our study show that similar to many centers, the etiology of HCM is often uncertain. In the absence of etiology, treatment aimed at the cause is either impossible or, at best, empirical.
Keywords: heart failure; hypertrophic cardiomyopathy; left ventricular hypertrophy; myectomy transthoracic echocardiography